An Exploratory Study of Reading Comprehension Difficulties Among Elementary-Levels of EFL University Learners - Nur Ilmi Wathoni; Rizki Alawiya; Muhammad Yani (JURNAL PENDIDIKAN BAHASA, 2026)
Reading comprehension is an essential skill in English as a Foreign Language (EFL) learning because it enables learners to understand written information, expand vocabulary knowledge, and support academic achievement. However, many EFL learners experience difficulties in comprehending English texts due to various linguistic and cognitive challenges. This study aimed to investigate the reading comprehension difficulties experienced by EFL learners and identify the factors contributing to these difficulties. The study employed a qualitative descriptive research design involving 26 first semester students from the English Education department in Indonesia. Data were gathered through reading assignments and open-ended surveys sent using Google Forms, enabling students to articulate their perspective. The findings revealed that learners experienced difficulties in four major areas: linguistic, cognitive, strategic, and affective factors. Linguistic difficulties included limited vocabulary knowledge and insufficient grammatical understanding. Cognitive difficulties involved identifying main ideas, understanding implied meaning, and integrating information across texts. Strategic difficulties were related to the limited use of effective reading strategies such as skimming and scanning, while affective factors included anxiety, confusion, and low confidence. The study concludes that reading comprehension difficulties among EFL learners are multidimensional and require comprehensive instructional approaches that address language knowledge, reading strategies, and emotional support simultaneously.